Microneedle-enhanced drug delivery: fabrication, characterization, and insights into release and permeation of nanocrystalline imiquimod - Meiser, Sophie Luise; Pielenhofer, Jonas; Hartmann, Ann-Kathrin; Stein, Lara; Dettweiler, Jule; Grabbe, Stephan; Radsak, Markus P.; Langguth, Peter (Frontiers in Drug Delivery, 2024)
Transcutaneous delivery systems bear several advantages over conventional needle-based injections. Considering the low bioavailability and poor water-solubility of imiquimod, a manufacturing process has been developed to incorporate imiquimod as suspended nanocrystals in different formulations. In this study, three formulations - fast-dissolving microneedle arrays that contain nanocrystalline imiquimod in a poly (vinyl)alcohol matrix and two semisolid preparations-were characterized and compared. The results show that microneedle arrays have an advantage over the semisolid preparations regarding in vitro release and permeation characteristics. Microneedle arrays facilitate ex vivo permeation, thus reducing the applied dose by 93% compared to the semisolid formulations. Additionally, the amount of imiquimod permeated after 24 h maintained the same level even when the contact time of the formulation with the skin is less than 1 hour. In conclusion, our results highlight the great potential of advanced microneedle based delivery systems and foster the further evaluation of this approach.